Multidisciplinary out‐patient treatment with monitoring by telemedicine for a large‐volume multifocal pyogenic liver abscess in times of the pandemic - Johannes J. Tebbe (Wiley, 2021)
Abstract Pyogenic liver abscesses represent one of the rarer, but potentially life‐threatening diseases of the liver. The treatment for large‐volume liver abscesses is usually multimodal with percutaneous drainage combined with several days of treatment in hospital. We are presenting a report on a male patient with type‐2 diabetes mellitus who suffered from a multifocal liver abscess (>10 cm). Due to the exceptional situation caused by the corona pandemic, the patient was treated conservatively with non‐standard treatment which involved a multidisciplinary team and out‐patient visits. Follow‐up to ensure the treatment would be successful was carried through dialogue with the GP responsible for the patient's care, as well as daily telemedicine visits. The daily telemedicine visits were supplemented by episodic follow‐up testing of laboratory values and contrast‐enhanced ultrasound scans (CEUS) of the liver. We show that purely conservative therapy can be successful in a case with a high risk of mortality by using a combination of close telemedical monitoring and proactive interdisciplinary collaboration with the GP.